Validity and Practicality of Android Ispring Suite Media with Problem-Based Learning in Pancasila Education - Suryani, Heriza Dwi; Reinita (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2025)
This research originated from observations conducted in elementary schools, which revealed that no learning media had been developed utilizing the Android-based iSpring Suite combined with the Problem Based Learning model for Pancasila Education in Grade IV. The study employs a Research and Development (R&D) approach following the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Data were gathered using validation sheets and response questionnaires. The validation instruments covered aspects of material, language, and media, while the response questionnaires involved feedback from both teachers and students. The study subjects included Grade IV students from SDN 16 Tanah Garam, SDN 20 Sinapa Piliang, and SDN 19 Tanah Garam. The findings indicated that the developed learning media was validated and considered highly valid, achieving an average validation score of 93.79%. Additionally, teacher and student responses showed that the media was practical for classroom use. Overall, learning through the Android-based iSpring Suite integrated with the Problem Based Learning model was confirmed to be both valid and practical for implementation in the learning process.